2018
DOI: 10.4041/kjod.2018.48.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single-dose, low-level laser therapy on pain associated with the initial stage of fixed orthodontic treatment: A randomized clinical trial

Abstract: ObjectiveThe aim of this study was to assess the analgesic effect of a single application of low-level laser therapy (LLLT) on spontaneous pain and pain on chewing after placement of initial archwires.MethodsForty-two patients (26 women, 16 men) were randomly recruited for this split-mouth randomized clinical trial. Each patient received super-elastic nickel-titanium (NiTi) initial archwires (0.012, 0.014, 0.016, and 0.018-inch [in]) in the maxilla for leveling and alignment for an interval of 4 weeks between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 31 publications
1
48
1
1
Order By: Relevance
“…Hence, it is generally referred to as "Cold Laser" or Low-level laser. 20,[3][4][5][6][7][8][9][10] Though the precise mechanism of its therapeutic action is obscure, it has been confirmed that its actions are at tissue, cellular and molecular levels.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, it is generally referred to as "Cold Laser" or Low-level laser. 20,[3][4][5][6][7][8][9][10] Though the precise mechanism of its therapeutic action is obscure, it has been confirmed that its actions are at tissue, cellular and molecular levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, infrared radiation of 940nm wavelength [8][9][10] and LLLT of wavelength close to lower end of infrared electromagnetic spectrum were used. As the infrared radiation has a low absorption coefficient in haemoglobin and water, it is generally agreed that it has deeper penetration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations